Performance of flax-FRP sandwich panels exposed to different ambient temperatures. (20th September 2019) - Mak, Kenneth; Fam, Amir
Highlights: FFRP stiffness and strength increase with decreasing temperature. FFRP-PIR SIP have an inverse relationship between temperature and load capacity. Within service limit states, FFRP-PIR SIPs respond the same between 20 °C and −20 °C. Abstract: Structural insulated panels (SIP), composed of an insulating foam core cladded with structural flax fibre-reinforced polymer (FFRP) skin, performs adequately in ambient conditions; however, natural fibres are susceptible to the environment. This study tests SIPs in different environmental conditions. Overall, the secondary tensile modulus of FFRP increased as temperature decreased, which translated to the SIP. For example, when the temperature decreased from 20 °C to −20 °C, the SIP's capacity increased by 28% and stiffness increased in the latter load-deflection response. Although this offers a larger margin of safety, there was no difference in performance across temperatures within normal service loads.